ONLINE SELLING AND BUYING FRAUD: THE LAW OF ELECTRONIC TRANSACTION PERSPECTIVE - Muhammad Kamran; Ahmadi Miru; Maskun Maskun (JCH (Jurnal Cendekia Hukum), 2021)
The rapid development of buying and selling online today is also followed by a high number of online based frauds. This study aims to determine the legal protection for consumers due to online buying and selling fraud. This research is a normative legal research using a statutory approach, a case approach, a conceptual approach, an analytical approach and a theoretical approach. The result of this study indicates that legal protection for consumers due to online buying and selling fraud creates responsibility for consumer losses in electronic transactions as regulated both in the ITE Law, Civil Code, Criminal Code and Consumer Protection Law. The consumer losses oblige the person who due to his fault published the loss has to compensate the loss. So the recommendation of the researcher is for the online buying and selling agreement is still prone to fraud, with this fraud, it issues legal consequences, the main cause of prone to the online buying and selling business fraud is because there are several parties who are not responsible for all the items sold.